Disc-halo gas outflows driven by stellar clusters as seen in multiwavelength tracers. Issue 2 (27th January 2023) - Vasiliev, Evgenii O; Drozdov, Sergey A; Nath, Biman B; Dettmar, Ralf-Jürgen; Shchekinov, Yuri A
ABSTRACT: We consider the dynamics of and emission from growing superbubbles in a stratified interstellar gaseous disc driven by energy release from supernovae explosions in stellar clusters with masses Mcl = 10 5 − 1.6 × 10 6 M⊙ . Supernovae are spread randomly within a sphere of rc = 60 pc, and inject energy episodically with a specific rate $1/130~M_\odot ^{-1}$ proportional to the star formation rate (SFR) in the cluster. Models are run for several values of SFR in the range 0.01 to 0.1 M⊙ yr −1, with the corresponding average surface energy input rate ∼0.04–0.4 erg cm −2 s −1 . We find that the discrete energy injection by isolated SNe are more efficient in blowing superbubbles: Asymptotically they reach heights of up to 3 to 16 kpc for Mcl = 10 5 − 1.6 × 10 5 M⊙, correspondingly, and stay filled with a hot and dilute plasma for at least 30 Myr. During this time, they emit X-ray, Hα and dust infrared emission. X-ray luminosities LX ∝SFR 3/5 that we derive here are consistent with observations in star-forming galaxies. Even though dust particles of small sizes a ≤ 0.03 μm are sputtered in the interior of bubbles, larger grains still contribute considerably ensuring the bubble luminosity $L_{\rm IR}/{\rm SFR}\sim 5× 10^7 \, L_\odot \, M_\odot ^{-1} ~{\rm yr}$ . It is shown that the origin of the North Polar Spur in the Milky Way can be connected with activity of a cluster with the stellar mass of ∼10 5 M⊙ and the SFR ∼ 0.1 M⊙ yr −1 some 25–30 Myr ago. Extended luminous haloes observed in edge-on galaxies (NGC 891 as an example) can be maintained by disc spread stellar clusters of smaller masses M * ≲ 10 5 M⊙ .